John B. Goodenough: Tribute to John B. Goodenough: From Magnetism to Rechargeable Batteries (Adv. Energy Mater. 2/2021). Issue 2 (14th January 2021) - Mauger, Alain; Julien, Christian M.; Armand, Michel; Zaghib, Karim
Abstract : As one of the recipients of the 2019 Nobel Prize in Chemistry, John B. Goodenough has made significant contributions across chemistry and physics including the development of critical cathode materials for lithium‐ion batteries, the understanding of d‐electron behavior in transition‐metal oxides, and transport properties of perovskites. In article number 2000773, Karim Zaghib and co‐workers review some of his scientific work demonstrating his mastery of chemistry and physics.